Atmospheric CO2 fertilization effects on biomass yields of 10 crops in northern Germany - Degener, Jan F. (Frontiers in Environmental Science, 2015)
The quality and quantity of the influence that atmospheric CO2 has on crop growth is still a matter of debate. This study's aim is to estimate if CO2 will have an effect on biomass yields at all, to quantify and spatially locate the effects and to explore if an elevated photosynthesis rate or water-use-efficiency is predominantly responsible. This study uses a numerical carbon based crop model (BioSTAR) to estimate biomass yields within the administrative boundaries of Niedersachsen in Northern Germany. 10 crops are included (winter grains: wheat, barley, rye, triticale - early, medium, late maize variety - sunflower, sorghum, spring wheat), modeled annually for the entire 21st century on 91,014 separate sites. Modeling was conducted twice, once with an annually adapted CO2 concentration according to the SRES-A1B scenario and once with a fixed concentration of 390 ppm to separate the influence of CO2 from that of the other input variables. Rising CO2 concentrations will play a central role in keeping future yields of all crops above or around today's level. Differences in yields between modeling with fixed or adapted CO2 can be as high as 60 % towards the century's end. Generally yields will increase when CO2 rises and decline when it is kept constant. As C4-crops are equivalently affected it is presumed that an elevated efficiency in water use is the main responsible factor for all plants.